2005
DOI: 10.1177/039463200501800105
|View full text |Cite
|
Sign up to set email alerts
|

Shock Induction by Arterial Hypoperfusion of the Gut Involves Synergistic Interactions between the Peripheral Enkephalin and Nitric Oxide Systems

Abstract: To determine whether critical splanchnic artery hypoperfusion can provoke systemic shock and to identify the roles of the peripheral opioid and nitric oxide (NO) systems in this process, various degrees of superior mesenteric artery hypoperfusion (SMA-H) were produced in anesthetized adult rabbits (n=40), and hemodynamic and metabolic indices were measured. Metabolic acidosis and irreversible hypodynamic shock occurred with SMA-H at levels representing 25-20% of mean baseline SMA blood flow. In 112 other rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These studies follow what shown by ours in 2005 [3] in rabbits developing hypodynamic systemic shock when the superior mesenteric artery (SMA) was hypoperfused at critical levels representing 25-20% of its mean baseline blood flow. We showed that the selective blockade of cardiovascular δ-opioid receptors by ICI 174864 or naltrindole improved haemodynamics, prevented shock irreversibility and reduced plasma nitric oxide (NO) levels; similar effects were obtained by selective inhibition of inducible NO synthase (iNOS) by AMT ( ± 2-amino-5,6-dihydro-6-methyl-4H-1,3-thiazine, HCl) but not by blocking opioid receptors other than the δ ones (e.g.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…These studies follow what shown by ours in 2005 [3] in rabbits developing hypodynamic systemic shock when the superior mesenteric artery (SMA) was hypoperfused at critical levels representing 25-20% of its mean baseline blood flow. We showed that the selective blockade of cardiovascular δ-opioid receptors by ICI 174864 or naltrindole improved haemodynamics, prevented shock irreversibility and reduced plasma nitric oxide (NO) levels; similar effects were obtained by selective inhibition of inducible NO synthase (iNOS) by AMT ( ± 2-amino-5,6-dihydro-6-methyl-4H-1,3-thiazine, HCl) but not by blocking opioid receptors other than the δ ones (e.g.…”
supporting
confidence: 87%
“…We showed that the selective blockade of cardiovascular δ-opioid receptors by ICI 174864 or naltrindole improved haemodynamics, prevented shock irreversibility and reduced plasma nitric oxide (NO) levels; similar effects were obtained by selective inhibition of inducible NO synthase (iNOS) by AMT ( ± 2-amino-5,6-dihydro-6-methyl-4H-1,3-thiazine, HCl) but not by blocking opioid receptors other than the δ ones (e.g. the κ 1 -receptors by nor-binaltorphimine) or by using drugs like fenoprofen and hydrocortisone [3]. Moreover, leu 5 and met 5 -enkephalins (ENK, specific activators of δ-opioid receptors), but not other physiological agonists, impaired haemodynamic function and increased plasma NO levels, when administered intravenously, much more during SMA hypoperfusion (SMAH) than in baseline conditions [3].…”
mentioning
confidence: 82%
“…The activity of the HDC enzyme is altered in various neurological diseases, treated and non-treated with therapeutical compounds. HDC is useful in studies in identification of histaminergic neurons and their function in the brain [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…(7)(8)(9) Recently, the expression of the IL-7 related cytokine, thymic stromal lymphopoietin (TSLP), has been shown to provide an AD-like phenotype (eczema and high serum IgE level) in mice expressing the transgene. (10)(11)(12)(13) Moreover, TSLP induces DC activation and maturation, suggesting a pivotal role of this cytokine as initiator of the allergic inflammatory process. (14)(15)(16)(17) TSLP-activated DC then migrates into the draining lymph nodes where they promote the differentiation of allergen-specific naïve CD4+ T lymphocytes to become effector Th2 cells.…”
Section: Introductionmentioning
confidence: 99%